A multi-site randomized controlled trial of a cognitive skills programme for male mentally disordered offenders: social-cognitive outcomes - Cullen, Alexis E.; Hodgins, Sheilagh (Psychological medicine, 2011)
Background. Cognitive skills programmes have been associated with improvements on psychometric measures and reductions in antisocial behaviour in mentally disordered oﬀenders (MDOs). However, to date there have been no randomized controlled trials (RCTs) of such programmes with this population. In the ﬁrst RCT of a cognitive skills programme with MDOs we aimed to determine if participation in the Reasoning and Rehabilitation (R&R) programme was associated with improvements in social-cognitive skills and thinking styles.